Effects of [NaBr] on the rate of intramolecular general base-assisted hydrolysis of N-(2 `-Hydroxyphenyl)phthalimide in the presence of cationic micelles: Kinetic evidence for the probable micellar structural transition - Khan, M.N.; Azri, M.H.R. (American Chemical Society, 2010)
Pseudofirst-order rate constants for aqueous cleavage of N-(2'-hydroxyphenyl)phthalimide (1), obtained at 0.001 M NaOH, 2 x 10(-4) M 1, 2% v/v CH(3)CN, and 30 degrees C, show a nonmonotonic decrease with the increase in the total concentration of cetyltrimethylammonium bromide ([CTABr](T)) within its range >= 9 x 10(-5)-<= 0.17 M. Similar observations have been obtained in the presence of the constant concentration of NaBr at <= 0.02 M. The values of k(obs) become independent of [CTABr](T) at >= 0.04 M CTABr and within a [NaBr] range of 0.0-0.005 M. These observations, in view of the pseudophase (PP) model of the micelle, reveal the presence of presumably spherical micelles at <= 3 x 10(-4) M CTABr in the presence of a constant concentration of NaBr within its range of 0.0-0.01 M. The average value of the CTABr micellar binding constant (K(S)) of ionized 1 (i.e., 1(-)), under these conditions, is (1.88 +/- 0.62) x 10(3) M(-1). The increase in [CTABr](T) at 4 x 10(-4) M causes a micellar structural transition from most likely spherical to cylindrical, which is evident from the increase in K(S) values from 3.46 x 10(3) to 11.4 x 10(3) M(-1) with the increase in [CTABr](T) from 4 x 10(-4) to similar to 1 x 10(-3) M in the absence of NaBr. The values of k(obs) at different [NaBr] and at a constant [CTABr](T) follow a kinetic relationship derived from an empirical equation coupled with a PP model of micelle. This relationship gives the value of a kinetic parameter, F(X/S), which represents the fraction of micellized S(-) (S(-) = 1(-)) transferred to the aqueous phase by the limiting concentration of X(-) (X(-) = Br(-)) through ion exchange X(-)/S(-). The value of F(Br/I) is 0.65 +/- 0.12